Cost-effectiveness of pan-genotypic direct-acting antiviral regimens for treatment of chronic Hepatitis C in the United States. (3rd May 2020) - Gordon, Stuart; Lee, Janet; Smith, Nathaniel; Dieterich, Douglas
ABSTRACT: Objectives: Given the goal of hepatitis C virus elimination by 2030, World Health Organization guidelines recommend treatment of chronic hepatitis C (CHC) with pan-genotypic direct-acting antivirals, such as sofosbuvir/velpatasvir (SOF/VEL), SOF/VEL/voxilaprevir (VOX) or glecaprevir/pibrentasvir (GLE/PIB). The study evaluated the cost-effectiveness of pan-genotypic regimens in initial (SOF/VEL or GLE/PIB) and re-treatment (SOF/VEL/VOX or GLE/PIB+SOF+ribavirin (RBV)) of CHC. Methods: A Markov state-transition model projected lifetime CHC health and economic outcomes from the US payer perspective. Model inputs were sourced from clinical trials or published literature and validated by hepatologists. Model outcomes included numbers of advanced liver disease events, life-years and quality-adjusted life-years (QALYs) gained, and total lifetime costs. One-way sensitivity analyses were performed on model results. Results: SOF/VEL followed by SOF/VEL/VOX resulted in comparable cure rates to the GLE/PIB treatment pathway (99.94% vs. 99.93%, respectively). SOF-based regimens provided similar QALYs at a lower lifetime cost versus a GLE/PIB treatment pathway (30, 749 vs. 36, 255), resulting in cost savings of 5, 506 per patient. Results were robust in sensitivity analyses. Conclusion: SOF/VEL followed by SOF/VEL/VOX leads to comparable cure rates in the overall CHC population relative to the GLE/PIB treatment pathway. Based on wholesale acquisition prices, the SOF/VEL treatment pathway led to lower lifetime costs.